Advances towards licensure of a maternal vaccine for the prevention of invasive group B streptococcus disease in infants: a discussion of different approaches. Issue 1 (31st December 2022) - Absalon, Judith; Simon, Raphael; Radley, David; Giardina, Peter C.; Koury, Kenneth; Jansen, Kathrin U.; Anderson, Annaliesa S.
ABSTRACT: Group B streptococcus ( Streptococcus agalactiae, GBS) is an important cause of life-threatening disease in newborns. Pregnant women colonized with GBS can transmit the bacteria to the developing fetus, as well as to their neonates during or after delivery where infection can lead to sepsis, meningitis, pneumonia, or/and death. While intrapartum antibiotic prophylaxis (IAP) is the standard of care for prevention of invasive GBS disease in some countries, even in such settings a substantial residual burden of disease remains. A GBS vaccine administered during pregnancy could potentially address this important unmet medical need and provide an adjunct or alternative to IAP for the prevention of invasive GBS disease in neonates. A hurdle for vaccine development has been relatively low disease rates making efficacy studies difficult. Given the well-accepted inverse relationship between anti-GBS capsular polysaccharide antibody titers at birth and risk of disease, licensure using serological criteria as a surrogate biomarker represents a promising approach to accelerate the availability of a GBS vaccine.